Os neo-rurais: capital humano estratégico de mudanças - Vargas, Yara Tarragó (2002)
A new social actor can be perceived in the agricultural scene of the state of Rio de Janeiro region serrana, neo-agricultural, enterprising the urban ones that if they ecological install in the field acting in defined agro-business. To analyze the participation of the neo-agricultural ones in the context, its consequences and implications is the pursued intention. Aiming at to extend the perception how much to the involved questions, they are boarded subjects as: globalization in the field, sustainable development, ecological economy. The enterprising expression is analyzed in its multiple and differentiated forms, as: production for market niches, agricultural tourism, plural, associative, as also some aspects pertinent politicians. Defined the planetary context and the enterprising expression, it is looked to draw the profile of the neo-agricultural one picking-up the influence of its insertion in the way. Its actions evidence an increasing process of social inclusion, propitiating better conditions of life for the set of places. From the perceived reality, how much to the possible effect of the recognition of this atypical exodus and to the integration of these actors to the politics of sustainable agricultural development are weaved.